SCIENTIFIC AND PEDAGOGICAL ACTIVITY OF SAYYID BURHONIDDIN TERMIZI - Abdunabiyev Sunnat Nemat ogli (Bright Mind Publishing, 2025)
This article explores the scientific and pedagogical activity of the prominent Islamic scholar and spiritual figure, Sayyid Burhoniddin Termizi. Known for his deep knowledge in Islamic jurisprudence, Sufism, and education, Sayyid Burhoniddin played a significant role in shaping the intellectual and spiritual environment of his time. The article provides an overview of his life, highlighting his educational background, major works, and influence on both contemporaries and later scholars. Special attention is given to his contributions to pedagogical thought, his methods of moral and spiritual education, and his role in the dissemination of Islamic values. The study also investigates his interaction with students and scholars, his emphasis on ethical teachings, and his legacy within the Islamic educational tradition. Through historical analysis and reference to manuscript sources, the article reveals the importance of Sayyid Burhoniddin’s approach in blending traditional Islamic sciences with practical moral instruction. This paper aims to emphasize the relevance of his ideas in modern educational discourse, especially in the context of spiritual upbringing and character development.
Keywords: Sayyid Burhoniddin Termizi, Islamic pedagogy, Sufism, spiritual education, moral development, Termiz scholars, Islamic heritage, pedagogical methods, historical analysis, educational legacy.